Detection of Citrus Greening Organism (Liberobacter Asiaticum) by Polymerase Chain Reaction - Mahmud Sara, Muh. Asaad (2001)
Citrus greening disease caused by greening organism (GO; Liberobacter asiaticum) is one of the most destructive diseases of citrus in Malaysia and Indonesia. To detect the GO in infected plant tissues, Polymerase Chain Reaction (PCR), an accurate, rapid and reliable detection method was applied to detect the 165 rONA fragments of the GO in leaves showing one of several typical symptoms of greening collected from GO-infected mandarin trees in Malaysia and Indonesia. In GO-infected mandarin trees, four typical symptoms of greening on leaves were observed , namely mottling (type I), mild chlorosis with green veins (type II), severe chlorosis with green veins (type III) and vein yellowing (type IV). Types II and III symptoms were mostly found in GO-infected mandarin trees in the field, followed by type I symptom, while type IV symptom was rare. Before PCR was used for the detection of GO in infected plant tissues, several experiments relating to the optimization of the PCR condition were conducted. Results indicated that the best sample of citrus tissues for DNA extraction was the midrib plus the petiole. This can be shown by more intense band observed after agarose gel electrophoresis. A positive amplification was still visible when the reaction mixture contained 10 ng of total DNA was used. Results of the optimization of the PCR condition indicated that the optimal PCR buffer for amplification of GO's DNA was the standard buffer containing 78 mM Tris-HCI (pH 8.8), 17 mM (NH4hS04, 10 mM ()-mercaptoethanol and 200)1g of Bovine Serum Albumin (BSA). The optimal concentrations of MgClz, d NTP, primer and Taq DNA polymerase to be used in reaction mixture were 1. 5 mM, 0.2 mM, 0.4uM, and 1 Unit, respectively. The optimal annealing temperature and num ber of cycles of PCR condition were 55°C and 40 cycles, respectively. The 16S rONA fragments of the GO in expected size of 1160 bp were detected in each typical symptoms. These fragments were amplified from DNA extracted from mandarin cultivars infected with the GO and were not amplified from DNA extracted from healthy trees. These fragments were also detected in insect vector (Diaphorina citn) collected from GO-infected mandarin trees and were not amplified from DNA extracted from healthy vector collected from Murayya paniculata using cetyl trimethyl ammonium bromide (CTAB) method for DNA extraction.